Answer
Las soluciones son:
a) \( x = -5 \) o \( x = 2 \)
b) \( x = \frac{4}{5} \) o \( x = 3 \)
c) \( x = -\frac{2}{3} \) o \( x = 2 \)
Solution
Solve the equation \( \frac{1}{x}-\frac{1}{x+3}=\frac{3}{10} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{1}{x}-\frac{1}{x+3}=\frac{3}{10}\)
- step1: Find the domain:
\(\frac{1}{x}-\frac{1}{x+3}=\frac{3}{10},x \in \left(-\infty,-3\right)\cup \left(-3,0\right)\cup \left(0,+\infty\right)\)
- step2: Multiply both sides of the equation by LCD:
\(\left(\frac{1}{x}-\frac{1}{x+3}\right)\times 10x\left(x+3\right)=\frac{3}{10}\times 10x\left(x+3\right)\)
- step3: Simplify the equation:
\(30=3x^{2}+9x\)
- step4: Swap the sides:
\(3x^{2}+9x=30\)
- step5: Move the expression to the left side:
\(3x^{2}+9x-30=0\)
- step6: Factor the expression:
\(3\left(x-2\right)\left(x+5\right)=0\)
- step7: Divide the terms:
\(\left(x-2\right)\left(x+5\right)=0\)
- step8: Separate into possible cases:
\(\begin{align}&x-2=0\\&x+5=0\end{align}\)
- step9: Solve the equation:
\(\begin{align}&x=2\\&x=-5\end{align}\)
- step10: Check if the solution is in the defined range:
\(\begin{align}&x=2\\&x=-5\end{align},x \in \left(-\infty,-3\right)\cup \left(-3,0\right)\cup \left(0,+\infty\right)\)
- step11: Find the intersection:
\(\begin{align}&x=2\\&x=-5\end{align}\)
- step12: Rewrite:
\(x_{1}=-5,x_{2}=2\)
Solve the equation \( \frac{4}{x}+\frac{2(x+1)}{3(x-2)}=4 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{4}{x}+\frac{2\left(x+1\right)}{3\left(x-2\right)}=4\)
- step1: Find the domain:
\(\frac{4}{x}+\frac{2\left(x+1\right)}{3\left(x-2\right)}=4,x \in \left(-\infty,0\right)\cup \left(0,2\right)\cup \left(2,+\infty\right)\)
- step2: Multiply both sides of the equation by LCD:
\(\left(\frac{4}{x}+\frac{2\left(x+1\right)}{3\left(x-2\right)}\right)\times 3x\left(x-2\right)=4\times 3x\left(x-2\right)\)
- step3: Simplify the equation:
\(14x-24+2x^{2}=12x^{2}-24x\)
- step4: Move the expression to the left side:
\(14x-24+2x^{2}-\left(12x^{2}-24x\right)=0\)
- step5: Calculate:
\(38x-24-10x^{2}=0\)
- step6: Factor the expression:
\(-2\left(3-x\right)\left(4-5x\right)=0\)
- step7: Divide the terms:
\(\left(3-x\right)\left(4-5x\right)=0\)
- step8: Separate into possible cases:
\(\begin{align}&3-x=0\\&4-5x=0\end{align}\)
- step9: Solve the equation:
\(\begin{align}&x=3\\&x=\frac{4}{5}\end{align}\)
- step10: Check if the solution is in the defined range:
\(\begin{align}&x=3\\&x=\frac{4}{5}\end{align},x \in \left(-\infty,0\right)\cup \left(0,2\right)\cup \left(2,+\infty\right)\)
- step11: Find the intersection:
\(\begin{align}&x=3\\&x=\frac{4}{5}\end{align}\)
- step12: Rewrite:
\(x_{1}=\frac{4}{5},x_{2}=3\)
Solve the equation \( \frac{1}{x}+\frac{1}{x^{2}}=\frac{3}{4} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{1}{x}+\frac{1}{x^{2}}=\frac{3}{4}\)
- step1: Find the domain:
\(\frac{1}{x}+\frac{1}{x^{2}}=\frac{3}{4},x\neq 0\)
- step2: Multiply both sides of the equation by LCD:
\(\left(\frac{1}{x}+\frac{1}{x^{2}}\right)\times 4x^{2}=\frac{3}{4}\times 4x^{2}\)
- step3: Simplify the equation:
\(4x+4=3x^{2}\)
- step4: Move the expression to the left side:
\(4x+4-3x^{2}=0\)
- step5: Factor the expression:
\(\left(2-x\right)\left(2+3x\right)=0\)
- step6: Separate into possible cases:
\(\begin{align}&2-x=0\\&2+3x=0\end{align}\)
- step7: Solve the equation:
\(\begin{align}&x=2\\&x=-\frac{2}{3}\end{align}\)
- step8: Check if the solution is in the defined range:
\(\begin{align}&x=2\\&x=-\frac{2}{3}\end{align},x\neq 0\)
- step9: Find the intersection:
\(\begin{align}&x=2\\&x=-\frac{2}{3}\end{align}\)
- step10: Rewrite:
\(x_{1}=-\frac{2}{3},x_{2}=2\)
Las soluciones de las ecuaciones dadas son:
a) \( x = -5 \) o \( x = 2 \)
b) \( x = \frac{4}{5} \) o \( x = 3 \)
c) \( x = -\frac{2}{3} \) o \( x = 2 \)
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution